Power generation from vinasse and press mud via anaerobic co-digestion a plant design - Dela Cruz, Alfonso Paolo F.; Leyson, Frances Gillian D.; Lintag, Rans Miguel N.; Matibag, Mica Samantha B.
The unreliability and instability of power generation in the Philippines - especially in Mindanao where most of the power plants in the region rely mostly on hydroelectric sources - causes a deficit of power in the country. Furthermore, 76% of the Philippine power generation comes from fossil fuels, and a huge %age of vinasse and press mud, industrial wastes from distilleries with very high biodegradable content, are not utilized. This provides an opportunity to develop a power generating technology that would address the demand of electricity through the use of biomass, specifically industrial wastes that would otherwise only be treated and disposed. Anaerobic co-digestion, which uses two or more types of biodegradable substrates in the liquid and solid phase to produce biogas, was chosen over mono digestion due to having a higher methane yield, increased process stability, optimal carbon to nitrogen ratio, increased biodegradable content, and proper pH adjustment. The plant is divided into four parts: feedstock preparation, biogas production and purification, combustion of biogas and power generation. Treatment of the raw materials is important in order to achieve the desired characteristics for the biogas production. Energy-rich organic waste materials are added to the digesters with excess capacity to ensure reliable production of biogas. The produced biogas in the anaerobic digesters undergoes purification processes such as absorption and distillation to yield higher purity methane gas. A combustion chamber then produces hot gases from the upgraded biogas which will be used to generate 24 MW of power. The design of the anaerobic digesters was patterned after the design of upflow anaerobic sludge blanket reactors, considering the residence time and conversion, which are 18 hours and 75.27%, respectively. Temperature is maintained in these digesters to ensure microbial stability. A box-type model combustion chamber based from Dr. Reyad Shawabkeh was used for the design of the fired heater. All pollutant concentrations in the effluent streams are within the standards and in accordance to DAO 2016-08, the Philippine Clean Water Act of 2004, and the Philippine Clean Air Act of 1999. From cost analysis, it was observed that the main cost drivers for the designed power plant are the equipment for fluid transport and the utility plant electricity. Annually, the plant will have a total sales revenue of 940,000 US Dollar. Due to the Renewable Energy Law, 32,000 US Dollar will be saved, which is 5% of the cost of goods sold. Taking into account all the costs, sales, and RE Law, the discounted payback period of the plant is observed at 15.5 years. Sensitivity analysis shows that payback is most sensitive to sales revenue. Hence, sales volume and pricing must be focused on during the operating years of the plant. For the break even analysis, cost of goods sold and sales revenue intersect at 40% of the designed plant capacity, which means the plant will start earning profit at this capacity. Assuming a 17-year plant life, the plant has a net present value of 5,000,000 USD and an IRR of 9.68% which is within the range of minimum acceptable rate of return of 8% to 12%. However, since the payback period is still on the 15th year of its operation, the designed plant is only potentially feasible.